Classical molecular dynamics investigations of biphenyl-based carbon nanomembranes - Mrugalla, Andreas; Schnack, Jürgen (Beilstein Journal of Nanotechnology, 2014)
Background: Free-standing carbon nanomembranes (CNM) with molecular thickness and macroscopic size are fascinating objects both for fundamental reasons and for applications in nanotechnology. Although being made from simple and identical precursors their internal structure is not fully known and hard to simulate due to the large system size that is necessary to draw definite conclusions.Results: We performed large-scale classical molecular dynamics investigations of biphenyl-based carbon nanomembranes. We show that one-dimensional graphene-like stripes constitute a highly symmetric quasi one-dimensional energetically favorable ground state. This state does not cross-link. Instead cross-linked structures are formed from highly excited precursors with a sufficient amount of broken phenyls.Conclusion: The internal structure of the CNM is very likely described by a disordered metastable state which is formed in the energetic initial process of electron irradiation and depends on the process of relaxation into the sheet phase.
Keywords: biphenyls; carbon nanomembranes; classical molecular dynamics

(untitled) - Geyer, W.; Stadler, V.; Eck, W.; Zharnikov, M.; Gölzhäuser, A.; Grunze, M. (Appl. Phys. Lett., 1999)

(untitled) - Turchanin, A.; Beyer, A.; Nottbohm, C. T.; Zhang, X.; Stosch, R.; Sologubenko, A.; Mayer, J.; Hinze, P.; Weimann, T.; Gölzhäuser, A. (Adv. Mater., 2009)

(untitled) - Angelova, P.; Vieker, H.; Weber, N.-E.; Matei, D.; Reimer, O.; Meier, I.; Kurasch, S.; Biskupek, J.; Lorbach, D.; Wunderlich, K.; Chen, L.; Terfort, A.; et al. (ACS Nano, 2013)

(untitled) - Turchanin, A.; Käfer, D.; El-Desawy, M.; Wöll, C.; Witte, G.; Gölzhäuser, A. (Langmuir, 2009)

(untitled) - Rhinow, D.; Weber, N.-E.; Turchanin, A. (J. Phys. Chem. C, 2012)

(untitled) - Heimel, G.; Romaner, L.; Zojer, E.; Brédas, J.-L. (Nano Lett., 2007)

(untitled) - Heimel, G.; Romaner, L.; Bredas, J.-L.; Zojer, E. (Langmuir, 2008)

(untitled) - Cabrera-Sanfelix, P.; Arnau, A.; Sanchez-Portal, D. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Marks, N. A. (Phys. Rev. B, 2000)

(untitled) - Marks, N. A.; Cooper, N. C.; McKenzie, D. R.; McCulloch, D. G.; Bath, P.; Russo, S. P. (Phys. Rev. B, 2002)

(untitled) - Powles, R. C.; Marks, N. A.; Lau, D. W. M. (Phys. Rev. B, 2009)

(untitled) - Tersoff, J. (Phys. Rev. B, 1988)

(untitled) - Brenner, D. W. (Phys. Rev. B, 1990)

(untitled) - Brenner, D. W.; Shenderova, O. A.; Harrison, J. A.; Stuart, S. J.; Ni, B.; Sinnott, S. B. (J. Phys.: Condens. Matter, 2002)

(untitled) - Zhang, X.; Beyer, A.; Gölzhäuser, A. (Beilstein J. Nanotechnol., 2011)

(untitled) - Amiaud, L.; Houplin, J.; Bourdier, M.; Humblot, V.; Azria, R.; Pradier, C.-M.; Lafosse, A. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Leung, T. Y. B.; Schwartz, P.; Scoles, G.; Schreiber, F.; Ulman, A. (Surf. Sci., 2000)

(untitled) - Azzam, W.; Fuxen, C.; Birkner, A.; Rong, H.-T.; Buck, M.; Wöll, C. (Langmuir, 2003)

(untitled) - Shaporenko, A.; Cyganik, P.; Buck, M.; Terfort, A.; Zharnikov, M. (J. Phys. Chem. B, 2005)

(untitled) - Bashir, A.; Käfer, D.; Müller, J.; Wöll, C.; Terfort, A.; Witte, G. (Angew. Chem., Int. Ed., 2008)

(untitled) - Matei, D. G.; Muzik, H.; Gölzhäuser, A.; Turchanin, A. (Langmuir, 2012)

(untitled) - Matei, D. G.; Weber, N.-E.; Kurasch, S.; Wundrack, S.; Woszczyna, M.; Grothe, M.; Weimann, T.; Ahlers, F.; Stosch, R.; Kaiser, U.; Turchanin, A. (Adv. Mater., 2013)

(untitled) - Qi, Y.; Çağın, T.; Kimura, Y.; Goddard, W. A., III (Phys. Rev. B, 1999)

(untitled) - Qi, L.; Zhang, H. F.; Hu, Z. Q. (Intermetallics, 2004)

(untitled) - Xie, L.; Brault, P.; Thomann, A.-L.; Bedra, L. (Appl. Surf. Sci., 2013)

(untitled) - Frey, S.; Rong, H.-T.; Heister, K.; Yang, Y.-J.; Buck, M.; Zharnikov, M. (Langmuir, 2002)

(untitled) - Waske, P. A.; Meyerbröker, N.; Eck, W.; Zharnikov, M. (J. Phys. Chem. C, 2012)

(untitled) - Nosé, S. (J. Chem. Phys., 1984)

(untitled) - Hoover, W. G. (Phys. Rev. A, 1985)

(untitled) - Kusnezov, D.; Bulgac, A.; Bauer, W. (Ann. Phys., 1990)

(untitled) - Mentrup, D.; Schnack, J. (Physica A, 2001)

(untitled) - Mentrup, D.; Schnack, J. (Physica A, 2003)